2022
DOI: 10.21831/jk.v6i2.49445
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, learning motivation, learning environment and its effect on online learning outcomes

Abstract: This study aimed to analyze e students’ psychological factor, namely self-efficacy, learning motivation and learning environments on the results of online physical education learning during Covid-19 at Senior High School in Padang, West Sumatera. This study used a quantitative method using a path analysis approach, with structural equations to find out the causality of the dimensions of self-efficacy, motivation, directly on learning outcomes of physical education, or indirectly through the learning environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, whereas the prior section shows that self-efficacy and retention are not directly associated with one another, Figure12shows that they are, and many previous studies explored this relationship. Studies on distance education or online learning have also revealed a relationship between self-efficacy and academic achievement(Li, 2020;Masrun & Rusdinal, 2022). This relationship shows that students' belief in their ability to achieve specific goals through online learning design or distance education can promote academic success.The next cluster shows a relationship between self-efficacy and mobile learning (see Figure9).…”
mentioning
confidence: 98%
“…Furthermore, whereas the prior section shows that self-efficacy and retention are not directly associated with one another, Figure12shows that they are, and many previous studies explored this relationship. Studies on distance education or online learning have also revealed a relationship between self-efficacy and academic achievement(Li, 2020;Masrun & Rusdinal, 2022). This relationship shows that students' belief in their ability to achieve specific goals through online learning design or distance education can promote academic success.The next cluster shows a relationship between self-efficacy and mobile learning (see Figure9).…”
mentioning
confidence: 98%